High-density genetic mapping of Fusarium head blight resistance and agronomic traits in spring wheat - Berraies, Samia; Cuthbert, Richard; Knox, Ron; Singh, Arti; DePauw, Ron; Ruan, Yuefeng; Bokore, Firdissa; Henriquez, Maria Antonia; Kumar, Santosh; Burt, Andrew; Pozniak, Curtis; N’Diaye, Amidou; et al. (Frontiers in Plant Science, 2023)
Fusarium head blight (FHB) has rapidly become a major challenge to successful wheat production and competitive end-use quality in western Canada. Continuous effort is required to develop germplasm with improved FHB resistance and understand how to incorporate the material into crossing schemes for marker-assisted selection and genomic selection. The aim of this study was to map quantitative trait loci (QTL) responsible for the expression of FHB resistance in two adapted cultivars and to evaluate their co-localization with plant height, maturity, days to heading, and awnedness. A large doubled haploid population (775 lines) developed from cultivars Carberry and AC Cadillac were assessed for FHB incidence and severity in nurseries near Portage la Prairie, Brandon and Morden in different years, and for height, days to heading, and maturity near Swift Current. An initial linkage map using a subset of 261 lines was constructed using 634 polymorphic DArT and SSR markers. QTL analysis revealed five resistance QTL on chromosomes 2A, 3B (2 loci), 4B and 5A. A second genetic map with increased marker density was constructed using the Infinium iSelect 90k SNP wheat array in addition to the previous DArT and SSR markers which revealed two additional QTL on 6A and 6D. The complete population was genotyped and a total of 6806 Infinium iSelect 90k SNP polymorphic markers were used to identify seventeen putative resistance QTL on 14 different chromosomes. As with the smaller population size and fewer markers, large effect QTL were detected on 3B, 4B and 5A that were consistently expressed over environments. FHB resistance QTL were co-localized with plant height QTL on chromosomes 4B, 6D and 7D, days to heading on 2B, 3A, 4A, 4B and 5A, and maturity on 3A, 4B, and 7D. A major QTL for awnedness was identified associated with FHB resistance on chromosome 5A. Nine small effect QTL were not associated with any of the agronomic traits, whereas thirteen QTL that were associated with agronomic traits did not co-localize with any of the FHB traits. There is opportunity to select for improved FHB resistance within adapted cultivars by using markers associated with complementary QTL.